Effect of high-content Yttria on the thermal expansion behaviour and ionic conductivity of a stabilised cubic Hafnia. Issue 15 (December 2020) - Sévin, Louise; Razafindramanana, Volatiana; Julian-Jankowiak, Aurélie; Justin, Jean-François; Mauvy, Fabrice; Rebillat, F.
Highlights: The increase of dopant content in the yttria-hafnia solid solution increases the lattice parameter of the fluorite phase however the thermal expansion coefficients remain constant even decrease along the range of dopant content. The increase in the dopant content up to 33 mol% in the yttria-hafnia solid solution reduces the ionic conductivity by two decades. A design trend of an Environmental and Thermal Barrier Coating for a combustion flame of 3000 K has been suggested. Abstract: The needs for space propulsion thruster induce the development of new designs and material compositions able to withstand 3000 K of flame combustion temperature. Cubic-stabilised hafnia appears as one of the most promising candidates to protect refractory materials in such conditions. Here, the influence of dopant content on the thermal expansion (473−1823 K) and ionic conductivity (600−1150 K) in highly doped-hafnia (12−33 mol% Y2 O3 ) with disordered cubic systems is reported. The composition and the homogeneity of the samples were carefully checked using crystallographic, chemical and spectroscopy analyses. Finally, the study of thermal and oxygen conductivity properties highlighted their dependence on the amount of dopant. The average thermal expansion coefficient was lowered from 11.3 to 10.9 10 −6 /K and the ionic conductivity decreased by two decades with 33 mol% of Y2 O3 by using the optimised substitution ratio. Interactions and local ordering of oxygen vacancies can explain this behaviour.